Antifungal terpenes from Hyptis suaveolens and alkaloids and saponin from Argemone mexicana - Maliwat, Leonora P. (Animo Repository, 1996)
Hyptis suaveolens afforded suaveolic acid, suaveolol and ursolic acid from the CHCl3 extract. The structures of suaveolic acid and suaveolol were identified by comparison of their 1H nmr spectral data with those found in the literature,11 while the structure of ursolic acid was identified by 1H nmr spectroscopy and FT-IR.Antimicrobial test conducted on suaveolol, suaveolic acid and ursolic acid using the paper disc diffusion method indicated that they are inactive against the bacteria Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus subtilis. However, it showed zones of inhibition against the fungi Candida albicans at a concentration of 100 ug/ml.Argemone mexicana afforded four interesting secondary metabolites from its CHCl3 extract: norchelerythrine, norsanguinarine, chelamine and sitosterol-B-D-glycoside. The separation was achieved by repeated gravity column chromatography (dry packing) and recrystallization. The structures of the compounds were elucidated by (1H, 13C, COSY) nmr, spectroscopy, and mass spectrometry.